Succeed or sink : business sustainability under globalisation - Rowley, Chris, 1959- (Chandos Asian studies series., 2012)
Aimed at business strategists, policy makers, researchers and adult learners, this book has an Asian perspective on business sustainability and is about understanding how recent developments and future actions in one part of the world will have a global impact. The book magnifies the concept of so-called 'globalisation' and examines the topic of business sustainability from a broad and integrated approach to business: encapsulating people, prosperity and the planet. Furthermore, it acknowledges the contributions, challenges and potential of not only the big corporate houses, but also the smaller ones, in this situation. Chapters discuss the benefits organisations can attain with better governance, and social and environmental practices are also analysed. Broad and integrated approach to business encapsulating people, prosperity and sustainabilityDetails recent developments and future actions in the areas of business sustainability and applicable more globallyWritten by highly knowledgeable and well-respected academician and practitioners in the field; a perfect blend of the best of both worlds.